2019
DOI: 10.1109/access.2018.2885120
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art Clustering Schemes in Mobile Ad Hoc Networks: Objectives, Challenges, and Future Directions

Abstract: Mobile ad hoc networks (MANETs) are self-organized networks without any fixed infrastructure. The topology changes are very frequent in MANETs due to nodes' mobility. The topology maintenance creates an extra overhead, as the mobility information of a single node is shared with all nodes in the network. To address the topology maintenance overhead problem in MANETs, the researchers proposed different cluster-based algorithms to reduce the size of a routing table. The clusters are formed to locally adjust the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 92 publications
(273 reference statements)
0
17
0
Order By: Relevance
“…Clustering algorithms in CRAHNs can be classified into different categories [4], [5], [10] such as (1) Dominatingset-based clustering [11]- [13], (2) Combined-metricsbased clustering [14], [15], (3) Common-control-channelestablishment-based clustering [16], [17], (4) Stability-based clustering [8], [18], (5) Energy-efficient clustering [19], [20] and (6) Spectrum-sense-improvement-based clustering [21]- [23]. Particularly, (1) The idea of dominating-set-based clustering is to find a minimum dominating set of CRAHNs which is used as a minimum routing space to optimize system performance in terms of control overheads, packet delivery ratio, delay, etc.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clustering algorithms in CRAHNs can be classified into different categories [4], [5], [10] such as (1) Dominatingset-based clustering [11]- [13], (2) Combined-metricsbased clustering [14], [15], (3) Common-control-channelestablishment-based clustering [16], [17], (4) Stability-based clustering [8], [18], (5) Energy-efficient clustering [19], [20] and (6) Spectrum-sense-improvement-based clustering [21]- [23]. Particularly, (1) The idea of dominating-set-based clustering is to find a minimum dominating set of CRAHNs which is used as a minimum routing space to optimize system performance in terms of control overheads, packet delivery ratio, delay, etc.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…Finally, a routing protocol was proposed with a channel assignment scheme based on node capacity to improve total throughput of control channels, end-to-end delay and packet delivery ratio. (5) In energy-efficient clustering, the aim is to reduce unnecessary energy consumption or balance energy consumption to prolong network lifetime by reducing transmission power, distance between members and cluster heads. In [19], the authors proposed a spectrum-aware cluster-based energy efficient multimedia routing (SCEEM) protocol for cognitive radio sensor network (CRSN) to overcome formidable limitations of energy and spectrum issues.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%
“…Another interesting finding in the literature is the clustering of MANETs as a mean to reduce the complexity of the routing table. M. Ahmad et al [18] provided a comprehensive survey about the different clustering algorithms that address this issue. It concluded that the effectiveness of the clustering algorithms depends on a set of specific parameters, which the nodes are remaining power, the relative mobility, the overhead data, the trust value, and the node reputation.…”
Section: Related Workmentioning
confidence: 99%
“…The other nodes can serve as ordinary nodes inside the cluster or gateways between clusters according to the cluster formation technique. Many algorithms have been proposed for dealing with the clustering problem [5]. An example of this type is the cluster-based routing protocol (CBRP) [6].…”
Section: Introductionmentioning
confidence: 99%